1984
DOI: 10.1111/j.1365-2362.1984.tb02104.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the concentration of free holo retinol‐binding protein in human plasma

Abstract: The total concentrations of retinol, retinol-binding protein and prealbumin were determined in plasma from twenty healthy men and sixty patients with various inflammatory conditions. These concentrations were all strongly correlated to each other and lower in the patient group. The concentration of free (not prealbumin-bound) holo retinol-binding protein, the presumed 'active' supplier of retinol to the tissues, was calculated. It was found not to be decreased in the patient group. Of the measured total concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Fex and Felding proposed that ‘holo (bound) RBP’ rather than total RBP relates to DA 20. This is consistent with holo-RBP being delivered to the cell surface receptor,21 22 In our study, holo-RBP was not determined.…”
Section: Discussionsupporting
confidence: 85%
“…Fex and Felding proposed that ‘holo (bound) RBP’ rather than total RBP relates to DA 20. This is consistent with holo-RBP being delivered to the cell surface receptor,21 22 In our study, holo-RBP was not determined.…”
Section: Discussionsupporting
confidence: 85%
“…The lower molar ratio in Indonesian neonates may be a reflection of lower glomerular filtration [5], A poorer correlation between cord PA and RBP level in premature neonates than in term infants has been demonstrated [12]. The concentration of RBP was strongly cor related with the concentration of PA in adults [6]. In the present study, a positive correlation was found between PA and RBP concentrations in Japanese neonates (r = 0.61; fig.…”
Section: Discussionsupporting
confidence: 62%
“…The retinol-RBP complex represents the form in which vita min A is mobilized from the liver and deliv ered to the many extrahepatic tissues that require vitamin A in order to maintain their normal differentiated structure and function [6], After delivery of vitamin A to the target cells, the RBP molecule loses its affinity for PA. Due to its small size the free RBP mole cule is filtered through the kidney glomeruli, reabsorbed by the proximal tubule cells and degraded [7], It has been demonstrated that the concen trations of RBP and PA are significantly lower in cord blood and neonatal blood than in adult blood [4,[8][9][10]. Sasanow et al [9] showed that maternal serum concentrations of RBP and PA do not markedly influence the levels from 25 to 42 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Free RBP is filtered and degraded in the kidney [Peterson, 1971]. Between 40% to 70% of plasma TTR is bound to RBP [Smith and Goodman, 1971;Fex and Felding, 1984]. The binding of RBP to TTR is independent of the binding of thyroxine [Raz and Goodman, 1969].…”
Section: Ttrmentioning
confidence: 99%